Analisis Penerapan Sistem Informasi Akuntasi Penerimaan dan Pengeluaran Kas terhadap Pengendalian Internal Kas pada PT. XYZ - Faisal, Ahmad; Yanthy Yosepha, Sri; Widodo, Sri; Bayu Purnomo, Lucky (DINASTI RESEARCH, 2025)
This study explores the impact of information technology utilization, the implementation of accounting information systems, and the application of internal control systems on the integrity of financial reports produced by companies. The integrity of financial reporting can be enhanced through the effective implementation of accounting information systems and internal controls. A well-designed accounting information system facilitates the production of high-quality financial statements that adhere to regulatory standards. Such a system must address key issues, including data security, timely information retrieval, report accuracy, report variety, and compliance with financial reporting standards. Enhancing the quality of financial reports can also be achieved by implementing a robust internal control system, which encompasses communication, monitoring, the control environment, risk assessment, and control measures. The integration of internal control systems, the application of information technology, and the establishment of effective accounting information systems collectively contribute to the improvement of financial report quality.